Social Factors Affecting Educational Success of Military Cadets - E. N. Karlova; V. E. Talynev (Высшее образование в России)
The article presents an analysis of social factors affecting educational success of cadets of military educational organizations based on the results of a sociological survey among cadets of the Air Force Academy and its branches (N=722). The aim of the study was to determine social characteristic of cadets which correlate with their educational success. According to the results of the survey, three groups of cadets were identified. The size of the groups corresponds to the data of the cadets’ objective academic performance. It was found that the greatest success is demonstrated by cadets for whom training in a higher military educational organization serves as a channel for intergenerational mobility and the continuation of the military professional development trajectory.It is revealed that the largest socio-professional group, which is a main supplier to the system of training future officers, is constituted by the representatives of the power unit, and the main factors of the educational success of cadets are 1) a developed military-professional orientation, 2) a high level of school performance, 3) living in large cities, 4) relatively high level of cultural capital and life experience.